Implementasi Metode Promethee Dalam Menentukan Penerimaan Beasiswa Miskin Pada SMKN 1 Bengkulu Tengah - Beni Tarnando (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2024)
Scholarships are a formiof assistance givenito students or students in the form of funds or money that will be used to help the costiof the educational process and ease the burden on students in taking the study period, especially the costi ssue, given a selective scholarshipiprogram. The provision of aid certainly has selective rules so that it results in manyi rulesioricriteriai that must be checked to determine who students are eligible to receive the scholarship. In this study to overcome the problem of improper distribution of poor scholarship funds at SMK Negeri 1 Bengkulu Tengah. The solution of this panel is to create a system in determining the provision of scholarship assistance to students at SMK Negeri 1 Bengkulu Tengah. By using the promethee method to distribute scholarships for the underprivileged. The Promethee method is one of the methods ofidecision-making techniques from several alternative options that exist, the conjecture and dominance of the criteria used, namely the criteria of age, parental income, parental status, parental occupation and education One method that can be used in determining the provision of scholarship assistance so that the results of the system using this promethee are expected to later help the school of SMK Negeri 1 Bengkulu Tengah iniselecting students who are eligible to receive scholarships.